Dampak Beasiswa pada Masa Studi Mahasiswa Universitas Al Azhar Indonesia Angkatan 2004-2006 - Zaqiatul Mardiah (Universitas Al Azhar Indonesia, 2011)
This paper investigates the effect of student aid programs introduced by Alazhar Indonesia University (UAI) on the study duration of bachelor program students who registered at the university in the academic years of 2004 – 2006. We apply semiparametric duration model with censored and complete data for this study. Estimation results, using a partial maximum-likelihood technique and considering several risk factors representing student aids, demographic, and individual traits, reveal that student aid programs are significantly abel to explain the variation of student’s study duration and also their probability to gaduate from UAI after certain period of study time. In general the higher the period of student aid received, the shorter the student’s study period. In addition there is empirical facts that regardless of their traits and characteristics, student’s probability to graduate will be bigger when his/her study period has exceed eight semester.